When polarization and disinformation go hand in hand: the discourse in the quality European press. - Teruel-Rodríguez, Laura; García-Faroldi, Livia (My University, 2023)
Disinformation is one of the most urgent threats facing contemporary societies around the world (Tandoc, Wei Lim, & Ling, 2017). There are numerous academics from Communication Sciences that address the phenomenon that was triggered by the election of Donald Trump as president of the United States in 2016 and after that has been decisive in European events such as Brexit, the management of the COVID19 pandemic or the war in Ukraine. The phenomenon of information disorders takes place in a highly polarized political scenario. The polarization among the social groups inside a country -as has been observed in movements such as the yellow vests in France (Souillard et al., 2020)- and both political and affective polarization (Gidron, Adams and Horne, 2020, Torcal and Comellas, 2022)- as is currently observed in Spain- are determining factors in public discourse. This research addresses the presence of informative disorders in a context of polarization through the analysis of the quality press of three important countries in Europe: France, Spain and the United Kingdom. The objective is to study the relationship between the two concepts (polarization and disinformation) in important newspapers from three countries with different media systems (Hallin and Mancini, 2003) between 2017 and 2022. This is an international diachronic study that makes it possible to compare more than three hundred articles from six newspapers representing different editorial lines. A quantitative discourse analysis has been carried out together with a qualitative frame study. According to the conference subtheme Media, Information and Communication, this proposal seeks to determine solutions to disinformation and polarization posed by the European press. That is, which are the actors that must intervene to stop this problem and what are the urgent practices that could be implemented.
Keywords: Información pública - Europa; Prensa y propaganda - Europa; Periodismo - Aspectos sociales - Europa; Polarización (Ciencias sociales); Europe; Disinformation; Polarization; Quality press; Frames